北極域研究拠点:グリーンランド天然資源研究所(GINR)における研究について - 杉山, 慎; 高橋, 美野梨; 末吉, 哲雄; Shin, Sugiyama; Minori, Takahashi; Tetsuo, Sueyoshi (2017)
第8回極域科学シンポジウム/横断セッション：[IA] 北極国際連携拠点の新展開 12月8日（金）国立極地研究所 2階大会議室 The Eighth Symposium on Polar Science/Interdisciplinary sessions: [IA] New insights of overseas research stations in the Arctic Fri. 8 Dec./2F Auditorium, National Institute of Polar Research conference object